Accountancy as a public service – evidence from Poland - Maruszewska, Ewa Wanda; Kołodziej, Sabina (Видавництво Львівської політехніки, 2011)
The article attempts to present nowadays Polish accountancy profession’s perception with special regards to public service. Nowadays, accountant provides data and takes active part in decision – making process in an enterprise. It should be emphasized that preparing financial statements is not only a process of implementing different techniques. It also requires social awareness with respect to area where business is done. Social awareness is one of characteristics that constitutes accountancy occupation as a profession [6]. The article also describes the results of a survey conducted among 213 participants, mainly graduate and postgraduate accounting and finance faculty students. Results of the survey proved that accountancy profession is regarded as public trust service, not only by employees working in financial department,s but also by those who do not deal with finance and bookkeeping issues within their work.
Keywords: accountant; public trust; accountancy profession; public service; professional ethic